Clustering Methods For Cluster-Based Routing Protocols In Wireless Sensor Networks: Comparative Study - Hassan, Ali Abdul Hussian; Md Shah, Wahidah; Jabbar Mohammed, Ali Abdul; Othman, Mohd Fairuz Iskandar (Research India Publications, 2017)
Wireless Sensor Networks are used in large area of applications since they can be suitable for various environments. It can function independently in the condition of harsh or risk places where a human's apparition is impossible or very hard. Nevertheless, the sensor's life-time is only related to their batteries, which are impossible for replacing or recharging. So, the energy-efficient routing protocols are very necessary and considers vital task for sensors networks. Various approaches of clustering algorithms are used to optimize the energy of routing protocols. Also, the clustering approaches support the scalability of Wireless Sensor Networks. In this paper, numerous energy efficient routing algorithms for hierarchical routing protocol in Wireless Sensor Networks have been discussed based on the clustering approaches. These approaches of clustering algorithms whether Distributed, Centralized, or Hybrid are reviewed very well, since the most of clustering algorithms have been developed by many researches based on these approaches. Our objective is exploring the literature to present a brief discussion of these algorithms, as well as examine and compare some of distributed, centralized and hybrid clustering algorithm based on several attributes. This work aims to give a clear vision for the developers and researchers about cluster-based hierarchical routing protocols, and how can classified the clustering approaches according to literatures.